Plantago major based ointment effect in wound healing murine model - Castro-Piedra, Silvia (2024)
Plantago major is a plant that has been attributed medicinal properties due to the diversity of compounds present in it. Crude extracts of this plant have been shown to aid in skin regeneration, stimulate cell proliferation, and exhibit antibacterial activity. This research aims to analyze the regenerative capacity of various extracts of P. major in an in vitro and in vivo model, including plant cell cultures, as biotechnology alternatives to produce metabolites of interest. Callus cultures were established in vitro using plant leaves cultured in M&S medium containing 50% salts and vitamins, supplemented with 2.5 mg/l TDZ, 3% m/v sucrose and pH 7. Different concentrations of P. major samples were tested to evaluate the in vitro cell migration. It was found that field extract treatment was the most efficient. Then, it was used to develop an ointment for analyzing its effect during skin wound healing phases in a murine model. The results of the in vivo regeneration model suggest that the P. major extract has anti-inflammatory properties which could increase the closure rate Thus, it is concluded that P. major species may be able to a positive effect on the acute phase of the skin wound healing.